2005
DOI: 10.1007/bf02897999
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and lifestyle factors related to quality of life in junior high school students

Abstract: Objectives: To analyze actual conditions of the quality of life (QOL) in junior high school students, we developed a questionnaire based on the PRECEDE-PROCEED model, and we conducted a survey by using this questionnaire.Methods: We conducted a workshop organized with 29 specialists on school health and community health to develop the questionnaire. The QOL outcome was assessed by the QOL ProfileAdolescent Version (QOLPAV). The subjects of the questionnaire surveys were 1600 general students in four junior hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The questionnaire for QOSL was modified from previous studies . A questionnaire based on the PRECEDE‐PROCEED model by Takano et al . was developed to analyze the QOL in junior high school students.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire for QOSL was modified from previous studies . A questionnaire based on the PRECEDE‐PROCEED model by Takano et al . was developed to analyze the QOL in junior high school students.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a positive improvement in lifestyle will increase quality of life. Research has indicated that increased physical activities can lead to changes in lifestyle; thus, exercise is the most straightforward and effective strategy for improving quality of life [23]. Exercise is known to improve peoples' satisfaction with the physical, psychological, social, and environmental aspects of quality of life; although increasing physical activities can only rectify health-endangering behaviors, it can still improve quality of life [24].…”
Section: Introductionmentioning
confidence: 99%